Workshop on ``Astronomy in High Education in Greece'' - Metaxa, M.; Seiradakis, J.; Hatzidimitriou, D.; Niarchos, P. (2010)
As one of the initiatives undertaken to promote Astronomy in Greece, particularly in view of the International Year of Astronomy 2009, the Hellenic Astronomical Society (Hel.A.S.), in collaboration with the Hellenic Association of the Laboratory Centers of Physical Sciences, organized a special workshop, under the umbrella of the 9th Hellenic Astronomical Conference, addressed to school teachers. The aim was to develop and promote teaching of Astronomy, which is currently an optional subject, offered during the second year of senior high school (Lyceum).